Neo Strategy to Use Fixed-Whiteboard Based on Students Thinking Process and Cultural Ethicaly in Learning Physics - Kristiyanto, Wahyu Hari; Prabowo, Prabowo; Kardi, Soeparman (International Journal of Active Learning, 2016)
Old guidelines to use the whiteboard stated that teachers were not allowed to write on the whiteboard while talking, because unethical if speak while back facing students. Findings about thinking process profile in information processing were presented with a whiteboard showed that the assimilation process is going to be supported, and audio-visual stimulants. This paper aims to describe the implementation of the latest strategies to use fixed-whiteboard based on students thinking process in learning physics with maximum the optimal thought processes and also maintain cultural ethics. This research was conducted through the use of guideline development assessment implementation fixed-slates based on the findings of the process of thinking and ethical culture in physics learning. The results showed that the latest strategy the use of fixed-whiteboard based on the thought process students and ethical culture in learning physics are (1) the assimilation process so that the display contents whiteboard is a material that is correct and does not cause cognitive conflict, (2) they are mutually reinforcing a combination of visual and audio so that the need to write while spelling, and (3) the thinking process to the stage of internalization that stage of the emergence of good information text / image / formula can be seen intact by all students by writing not cover impressions. The implementation results show the subject has been able to implement the latest strategies use fixed-whiteboard with both categories. The conclusions of this study that the use of the latest strategies fixed-whiteboard can be used for the presentation of information which is more than usual for students according to their thinking process and also maintain cultural ethics. The implication of this research is for Workforce Education Institutions need to equip student teachers with the skills to use the whiteboard based on the latest strategy.How to CiteKristiyanto, W. H., Prabowo, P. & Kardi, S. (2016). Neo Strategy to Use Fixed-Whiteboard Based on Students Thinking Process and Cultural Ethicaly in Learning Physics. International Journal of Active Learning, 1(1).